Prevalence of Erythromycin and Inducible Clindamycin Resistance in Staphylococci isolated from Clinical Samples in Western Nepal: Implications for Antimicrobial Stewardship - Shah, Rajesh; Myneedu, Vithal Prasad; Jha, Rakesh Kumar; Pokhrel, Sandeep; Karn, Subhash Lal; Neupane, Ganesh Prasad (Medical Journal of Eastern Nepal, 2026)
Background Staphylococci are major opportunistic pathogens with increasing antimicrobial resistance. Inducible clindamycin resistance (iMLSB) is often undetected by routine susceptibility testing, leading to treatment failure. In Nepal, data on iMLSB are limited and D-testing is not routinely performed. Objectives To determine the prevalence of erythromycin resistance and inducible clindamycin resistance among clinical staphylococcal isolates at a tertiary care hospital in western Nepal, and to evaluate methicillin resistance and multidrug resistance patterns. Methods A cross-sectional study was conducted from May 2024 to April 2025. A total of 374 non-duplicate staphylococcal isolates were identified by standard microbiological methods. Antimicrobial susceptibility testing was performed by Kirby-Bauer disc diffusion per CLSI 2024 guidelines. Methicillin resistance was detected using cefoxitin, and inducible clindamycin resistance was detected by the D-test. Results Staphylococcus aureus accounted for 293 (78.3%) isolates and coagulase-negative staphylococci (CoNS) for 81 (21.7%). Methicillin resistance was present in 57.7% of S. aureus (MRSA) and 63.0% of CoNS (MRCoNS). Multidrug resistance was observed in 43.7% of S. aureus and 38.3% of CoNS. Erythromycin resistance was 56.3% in S. aureus and 60.5% in CoNS. Among all isolates, the D-test revealed iMLSB in 35.6%, cMLSB in 43.6%, and MS phenotype in 20.9%. All isolates were susceptible to linezolid and vancomycin. Conclusions There is a high prevalence of methicillin resistance, multidrug resistance, and inducible clindamycin resistance among staphylococcal isolates. Routine D-testing is essential to detect iMLSB and avoid clindamycin treatment failure.